The influence of dipyridylamine-carbazole based bipolar host materials for green PHOLEDs. (November 2019) - Park, So-Ra; Kim, Su-Mi; Choi, Yongseon; Lee, Ja Yeon; Lee, Ji-Hoon; Suh, Min Chul
Abstract: The series of new bipolar host materials with dipyridylamine and carbazole moieties connected to the triazine core unit were synthesized for green phosphorescent organic light-emitting diodes (PHOLEDs). Especially, we controlled the hole transporting behaviors by attaching different connectivity of carbazole moieties attached to the triazine core in new synthetic host materials. From this approach, we found that triazine derivatives with dipyridylamine-carbazole based substituents exhibited moderately high glass temperature above 139 °C as well as relatively high triplet energy (T1 > 2.78 eV). With those bipolar host materials, we prepared green PHOLEDs. And the new synthetic dipyridylamine-carbazole based triazine derivative, [4, 6-bis(9-phenyl-9 H -carbazol-3-yl)- N, N -di(pyridin-2-yl)-1, 3, 5-triazin-2-amine (3-BCTPy) ] showed relati-vely high device efficiencies, up to 70.6 cd/A and 18.9% (external quantum efficiency, EQE) when we utilized it as a host materials and bis(2-phenylpyridine)(acetyl-acetonato) iridium (III) [Ir(ppy)2 (acac)] as a dopant. Graphical abstract: Image 1 Research Highlight : Highly efficient green PHOLED devices fabricated with new synthetic host materials. Bipolar properties originated from carbazole and dipyridyl amine moieties. High triplet energy greater than 2.78 eV.